Designing Strategies and Answering the Challenges of the Implementation of PERMENKOP-UKM Number 8 of 2023 on KSPPS and Sharia Financing (KSPPS) Merapi Husada's Determination "TERASA" - Sumino; Tho'in, Muhammad; Marimin (International Journal of Seocology, 2024)
KSPPS is a sharia financing cooperative or better known as (KSPPS) is a cooperative that has savings, borrowing, and financing business activities in accordance with sharia principles, including managing zakat, infaq, alms, and waqf. The purpose of this research is to find out how the role of KSPPS in community economic empowerment and the challenge of building a TERASA KSPPS strategy in Sleman, Yogyakarta Province in answering the challenges of regulations that have been circulated by the Ministry of Cooperatives and MSEs. Of course, this change in regulations will greatly modify various KSPPS governance policies in the future. KSPPS as one of the pillars of the sharia economy in Indonesia that has the potential to be developed. This research is a field research that uses qualitative descriptive. In collecting data, the author uses the interview method as a guideline for KSPPS TERASA employees in Sleman Yogyakarta, while documentation is carried out by recording or data obtained from KSPPS TERASA such as history, organizational structure, and financing at KSPPS TERASA. This article aims to build on previous studies by presenting a critical study of KSPPS's strategies and strategies in innovating in regulatory changes in accordance with global economic changes. This research uses a qualitative method that is expected to provide benefits in cooperative practice in Indonesia.